Revisiting Rancière's Concept of Intellectual Emancipation in Vocational Educational and Training Practices - Gisselle Tur-Porres; Danny Wildemeersch; Maarten Simons (Universidade de Lisboa, 2020)
The paper discusses the emancipatory potential of Uruguayan Vocational Educational and Training (VET) practices, usually associated with job discourses, skills and training. In doing so, we revisit Rancière's work concerning intellectual emancipation to provide us with a guide to connect with the phenomena studied, as a lens to look at and to problematize emancipation in concrete practices on a heuristic level. Thus, the paper is structured as follows. First, we describe the context of Uruguayan VET practices. Second, we discuss Rancière's key concepts about emancipation in education. Third, we craft a conversation between the empirical and theoretical work, in view of exploring concrete VET practices from the axiom of equality. Last, the text concludes with a reflection on new meanings regarding Rancière's intellectual emancipation that deserve further attention and allow us to identify other forms of emancipatory potential in VET practices, to move beyond its currently predominant functionalist understanding.